Heart Rate Monitoring and Stimulation with the Internet of Thing-Based (IoT) Alquran Recitation - Ilham, Dirja Nur; Hardisal, Hardisal; Balkhaya, Balkhaya; Candra, Rudi Arif; Sipahutar, Erwinsyah (Politeknik Ganesha Medan, 2019)
Heart rate or pulse is an important parameter used to determine a person's mental state because when the heartbeat is abnormal, it is necessary to make further efforts to prevent undesirable things from happening. In this study, researchers plan to design the Heart Rate Monitoring and Stimulation with the Internet of Thing-Based (IoT) Qur'an Recitation. The steps taken to design a monitoring system and stimulate the human heartbeat are to design hardware and software. The sensor used is a pulse heart rate sensor as a heart rate detector processed by Arduino-based NodeMCU V3, the test results and measurements will be sampled using smartphone media. Data collection process; polytechnic students as objects taken by their heart rate data, the data collection process was carried out twice, the morning before the lecture began and the afternoon after the lecture process was complete, the testing process was done by taking data using a smartphone and turning on the Quran recitation for 2 minutes. Research is expected to be an stimulus indicator of heart rate, so that the heart rate is more relaxed and calm